Evaluation of insecticides at different stages of plant growth for management of major pests in rice: Pests management with different chemical application methods - Kolandhaivelu, Karthikeyan (ORYZA-An International Journal of Rice, 2025)
An experiment was conducted under the All India Rice Improvement Project during the kharif seasons of 2021, 2022, and 2023 to assess the effectiveness of various insecticide application methods against major insect pests in rice. Thirteen treatments, including different combinations of seed treatment, nursery drenching, and main field applications of granular insecticides at 25 and 60 days after transplanting (DAT), were evaluated along with an untreated control, using a randomized block design with three replications. The pooled results over three seasons indicated that stem borer (dead heart) incidence was lowest with main field application of cartap hydrochloride (mean damage 1.60%), followed by seed treatment with thiamethoxam combined with main field application of cartap hydrochloride (2.08%), resulting in 83.88% and 79.05% reduction over control, respectively. White ear incidence was minimum with seed treatment using thiamethoxam plus main field application of cartap hydrochloride (17.31%), followed by main field application of cartap hydrochloride alone (19.83%), reducing damage by 48.59% and 41.10% over control, respectively. Nursery application of fipronil a week before transplanting recorded the lowest gall midge incidence (19.40%), followed by seed treatment plus main field application of fipronil (20.95%), with reductions of 43.02% and 38.47% over control. Whorl maggot and leaf folder incidences were also effectively reduced by seed treatment with main field application of cartap hydrochloride. The highest grain yield (3704 kg ha-1) was achieved with main field application of chlorantraniliprole, followed by fipronil nursery treatment combined with chlorantraniliprole, yielding 3568 kg/ha, with 18.38% and 14.03% increases over control, respectively. These findings demonstrate that integrated insecticide application strategies significantly minimize pest incidence and enhance rice productivity.